Hazards induced by anthropogenic activities, a lesson learned from recent underground construction works - K. Elbaz; S.L. Shen; W.C. Cheng (International Association of Lowland Technology, 2019)
Due to the expansion of underground constructions in urban areas, numerous hazards caused by anthropogenic activities have occurred in recent years. These hazards cause catastrophic failures which could pose a danger to life and property. Therefore, it is important to investigate the required knowledge to prevent these hazards. Five anthropogenic hazards that occurred due to the underground construction works are discussed; in order to identify risks and mitigate their adverse impacts in the future projects. According to the field investigations, it was found that there were many reasons for the underground construction failures caused by anthropogenic activities such as: faults in design and implementations, grouting material, leakage water, erosion, soil deterioration, and inadequate ground improvement. The understanding of these cases provides a wealth of experience and guidance for future excavations works.